Pendampingan Pendokumentasian Bahasa: Kata-Kata Bijak Bahasa Wolio dan Istilah Maritim Bahasa Kaera - Suhandano, Suhandano; Wijana, I Dewa Putu; Arimi, Sailal (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
Indonesia is known as the country with the most living language assets in the world after Papua New Guinea. However, one-third of the 718 indigenous languages in Indonesia are vulnerable and even threatened with extinction. Most of these languages are spoken in the central and eastern parts of Indonesia. Regarding efforts to protect, preserve and develop these vulnerable languages, the team of Program Studi Magister Linguistik, FIB, UGM took the initiative to provide language documentation assistance to the researchers and people in the Language Office (KB) of Nusa Tenggara Timur and the Language Office (KB) of Sulawesi Tenggara. Such facilitating and mentoring methods that were conducted include: firstly, observing and mapping the language aspects from the existing languages in NTT and Sultra to be decisively documented, secondly, model of providing assistance for documentation efforts, and thirdly, the writing form of documentation. After completing the facilitating and mentoring processes, it was expected that the researchers and documentation increased their passions and motivation in documenting the language aspects, their theoretical and methodological capacity in language documenting activities, and the number of documented languages. Besides, there was an increase of cooperation between Kantor Bahasa NTT and Sultra with Program Studi Magister Linguistik UGM. The results of this community service at the Language Office in NTT and Sultra show some completed activities i.e., (1) the identification of the legal basis for documenting the languages and mapping the potential language in NTT and Sultra to be documented, (2) the decision to document the linguistic aspects of maritime terms of the Kaera language in NTT, and words of wisdom or traditional expressions in Wolio language in Sultra, (3) the increase in the capacity of mentoring functions such as facilitating, presenting, feedback responding, delegating, participating, and inferencing, and (4) in addition to improving the ethics of mentoring, the teams worked together in terms of equality, cooperation and working together, and sustainability. ==== Indonesia dikenal sebagai negara dengan aset kekayaan bahasa terbanyak di dunia setelah Papua Nugini. Namun demikian, sepertiga dari 718 bahasa daerah di Indonesia itu mengalami kerentanan bahkan ancaman kepunahan. Kebanyakan bahasa itu berada di wilayah Indonesia Tengah dan Timur. Sebagai upaya pelindungan, pelestarian, dan pengembangan bahasa yang rentan ini, Tim Pengabdian Prodi Magister Linguistik berinisiatif melakukan pendampingan pendokumentasian bahasa terhadap tim KB di Nusa Tenggara Timur dan KB Sulawesi Tenggara. Metode pendampingan yang dilakukan adalah, pertama, menyangkut penjajakan atau pemetaan aspek kebahasaan yang perlu didokumentasikan oleh tim KB NTT dan KB Sultra; kedua, model pendampingan terhadap upaya pendokumentasian; dan ketiga, wujud penulisan hasil pendokumentasian. Setelah mengikuti proses pendampingan, diharapkan muncul peningkatan gairah dan motivasi pendokumentasian bahasa bagi para peneliti di dua KB tersebut, di samping peningkatan pengetahuan teoretis dan metodologis di bidang linguistik, peningkatan jumlah aspek bahasa yang didokumentasi, serta peningkatan kerja sama antarlembaga bahasa tersebut bersama Program Studi Magister Linguistik UGM. Hasil dari pengabdian pada Kantor Bahasa di NTT dan Sultra ini menyangkut beberapa pokok kegiatan, yaitu teridentifikasinya landasan hukum dan potensi bahasa di NTT dan Sultra terkait dokumentasi bahasa, diputuskannya aspek kebahasaan yang didokumentasi adalah istilah maritim bahasa Kaera di NTT dan kata-kata bijak atau ungkapan bahasa Wolio di Sulawesi Tenggara, dan terjadinya peningkatan kapasitas fungsi pendampingan seperti pemfasilitasian (facilitating), pemaparan (presenting), pemberian umpan balik (feedback responding), pewakilan tim (delegating), pengerjasamaan (participating), dan pengambilan kesimpulan (inferencing), di samping peningkatan etika pendampingan, yaitu kesetaraan, kerja sama, dan sama-sama bekerja, serta keberlanjutan.